2011
DOI: 10.1159/000330737
|View full text |Cite
|
Sign up to set email alerts
|

Stereological Estimation of Epidermal Volumes and Dermo-Epidermal Surface Area in Normal Skin

Abstract: Quantitative morphological studies of the healthy epidermis are essential in providing a range of parameter estimates that can be considered within the range of normality. Stereology is a set of statistical tools that provides potentially unbiased and precise estimates of 3-dimensional tissue characteristics from 2-dimensional sections. We set out to establish reference values for the volume of the viable epidermis contained within a four-millimetre punch biopsy (Vepi), the volume of the stratum cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
0
3
0
3
Order By: Relevance
“…Os estudos utilizando o delineamento estereológico concentram-se particularmente nas áreas de desenvolvimento embrionário (ZHANG, 2018), evolução (BOGGILD, 2018), patologia (ASHKANI-ESFAHANI et al, 2019) e neurociências (YURT,2018). Em dermatologia veterinária, é escassa sua empregabilidade, apesar do potencial para utilização (KAMP et al, 2009;MARTINS et al, 2010;KAMP et al, 2011).…”
Section: Desenvolvimentounclassified
See 1 more Smart Citation
“…Os estudos utilizando o delineamento estereológico concentram-se particularmente nas áreas de desenvolvimento embrionário (ZHANG, 2018), evolução (BOGGILD, 2018), patologia (ASHKANI-ESFAHANI et al, 2019) e neurociências (YURT,2018). Em dermatologia veterinária, é escassa sua empregabilidade, apesar do potencial para utilização (KAMP et al, 2009;MARTINS et al, 2010;KAMP et al, 2011).…”
Section: Desenvolvimentounclassified
“…De uma forma geral, as camadas e estratos da pele têm sido objeto de muitos estudos morfológicos e ultraestruturais, tanto pela variabilidade entre as espécies, quanto às funções imunológica, farmacodinâmica e farmacocinética cutânea (HUSSAIN, 2019;CHANG, 2017;AGARWAL, 2019;LOGGER, 2019). Em medicina veterinária, dado o elevado número de espécies estudadas, tais características tornam-se ainda mais relevantes, haja visto que as variações de celularidade, densidade celular, volume celular e tecidual, influenciam na fisiologia cutânea e, consequentemente, na rotina clínica para a espécie (KAMP et al, 2011).…”
Section: Introductionunclassified
“…Dermoscopy and RCM are considered complementary tools in the management of skin tumors, and RCM has been demonstrated to be particularly useful in the diagnosis of lesions for which dermoscopy can be challenging, as is the case with nonpigmented skin tumors [8,9,10,11,12,13,14]. However, since RCM has a limit in the visualization in depth (depth penetration is up to 300 µm under the skin surface), currently the evaluation of nodular lesions is not considered an indication for RCM [7,15]. Only a few studies have evaluated the effectiveness of RCM in the assessment of pigmented nodular lesions [16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have further demonstrated the ability of collagen to assemble into a network, which determines the strength and elasticity of healthy skin, can act as a template that defines cell behavior and tissue functions, directs the wound healing process and restores normal structure and function to skin previously damaged by injury or disease [2,3,4,5,6,7,8]. Although the present morphology studies that mostly built up on the 2-dimensional scale have achieved many advances concerning dermal tissues and the difference between normal tissue and scar tissue [9], the structural characteristic of the dermal tissue is still unknown, which impedes the progress of quantitative morphology studies [10]. Furthermore, in skin tissue engineering research, the ideal structure of the scaffold for cell behavior still needs to be clarified.…”
Section: Introductionmentioning
confidence: 99%